2021
DOI: 10.1007/s13280-021-01639-2
|View full text |Cite
|
Sign up to set email alerts
|

Between uncertainty and hope: Young leaders as agents of change in sustainable small-scale fisheries

Abstract: The path to sustainable small-scale fisheries (SSF) is based on multiple learning processes that must transcend generational changes. To understand young leaders from communities with sustainable SSF management practices in Mexico, we used in-depth interviews to identify their shared motivations and perceptions for accepting their fishing heritage. These possible future decision-makers act as agents of change due to their organizational and technological abilities. However, young people are currently at a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Similar to the findings of Espinoza‐Tenorio et al. (2022) in Mexico, climate change stressors are likely to threaten the ability of youths to continue in SSF. Moreover, after two decades of decline in fish catch, starting in 2009, Neis et al.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Similar to the findings of Espinoza‐Tenorio et al. (2022) in Mexico, climate change stressors are likely to threaten the ability of youths to continue in SSF. Moreover, after two decades of decline in fish catch, starting in 2009, Neis et al.…”
Section: Discussionsupporting
confidence: 75%
“…Lack of access to climate-smart innovations, tools and information were some of the concerns raised by potential successors as the reason for not desiring to participate in fisheries-related activities in the future. It has been established elsewhere by Espinoza-Tenorio et al (2022) in Mexico that youths engaged in SSF used social network platforms like Facebook to get fishing information. We found that access to subsidised or low-priced innovative fishing methods, tools and information was positively associated with potential successors' decisions to succeed in fish harvesting activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of some oceanographic monitoring data, fishers do not yet independently analyze it and often rely on external collaborations in order to maximize its value (Fulton et al, 2019)this highlights the potential for further investment in human capital. Yet, this has motivated the younger population to become advocates for the cause (Espinoza-Tenorio et al, 2021). In cases where Mexican fishers have been involved in the ecological monitoring of marine reserves, participants have also reported personal growth in areas ranging from environmental awareness to publicspeaking skills (Quintana et al, 2020), which has anecdotally enhanced their negotiating power with seafood buyers and policy-makers.…”
Section: Human Capitalmentioning
confidence: 99%